Metaphor Translation in Chinese Documentaries: A Case Study of 'A Bite of China’ - Yujie, Cai; Abdullah, Sharmini; MKM Mohamed Ibrahim3, Siti Balkis (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This study explores the translation of metaphors in the subtitles of the Chinese documentary A Bite of China, using Newmark's metaphor translation procedures as a guiding framework. Documentaries are vital for cultural exchange and shaping international perceptions, making accurate subtitle translation crucial. Despite the growing popularity of Chinese documentaries, their subtitles often suffer from inconsistencies and lack a solid theoretical foundation. This results in translations that may be inaccurate or fail to adhere to established principles, potentially diminishing their ability to convey the intended message and cultural details to global audiences. The study seeks to investigates the extent to which metaphors are used in the documentary's subtitles and identify the types of metaphors in the subtitles of the documentary translated from Mandarin into English. By examining the relationship between metaphor translation and subtitle translation, this study emphasizes the critical role of precise translations in promoting Chinese culture internationally and enhancing the global reception of Chinese documentaries. Kajian ini meneroka terjemahan metafora dalam sari kata dokumentari China, A Bite of China, dengan menggunakan prosedur terjemahan metafora Newmark sebagai kerangka panduan. Dokumentari memainkan peranan penting dalam pertukaran budaya dan pembentukan persepsi antarabangsa, menjadikan terjemahan sari kata yang tepat amat penting. Walaupun dokumentari China semakin popular, sari katanya sering menghadapi masalah ketidakkonsistenan dan kekurangan asas teori yang kukuh. Ini mengakibatkan terjemahan yang mungkin tidak tepat atau gagal mematuhi prinsip yang telah ditetapkan, yang berpotensi mengurangkan keupayaan untuk menyampaikan mesej dan butiran budaya yang dimaksudkan kepada audiens global. Kajian ini bertujuan untuk menyiasat sejauh mana metafora digunakan dalam sari kata dokumentari tersebut dan mengenal pasti jenis-jenis metafora dalam sari kata yang diterjemahkan daripada bahasa Mandarin ke bahasa Inggeris. Dengan meneliti hubungan antara terjemahan metafora dan terjemahan sari kata, kajian ini menekankan peranan penting terjemahan yang tepat dalam mempromosikan budaya China di peringkat antarabangsa dan meningkatkan penerimaan global terhadap dokumentari China.